Unfolding recognition: an empirical-theoretical contribution to the concept. Issue 2 (4th May 2019) - Sebrechts, Melissa; Tonkens, Evelien; Da Roit, Barbara
ABSTRACT: The past decades have witnessed growing interest in the concept of recognition, in social movements as well as in social theory. While the 'recognition turn' has made recognition a cornerstone in social and political philosophy, empirical interest – in sociology, anthropology and business studies – remains limited and has mainly focused on misrecognition and disrespect. As a result, recognition as a theoretical ideal remains largely divorced from the lived and messy realities of people's everyday search for recognition. This article addresses this lacuna. Based on long-term participant observation and interviews with professionals and young men with mild intellectual disabilities working in sheltered employment projects in the Netherlands, it examines everyday practices of claiming and receiving recognition, how recognition is shaped by the institutional environment of sheltered work, and how it is achieved or subverted in everyday interactions between young men and professionals. Our contribution to the literature lies in our empirical finding that misrecognition is often enfolded in recognition. By stating that misrecognition is enfolded in recognition, we mean that an instance of recognition coincides with, and likely depends on, some form of misrecognition. While focusing on the messiness and ambivalence of recognition in everyday life may dilute it as an ideal, acknowledging its dark side opens the path to a more nuanced understanding of the dynamic in which misrecognition, rather than being its opposite, is enfolded within recognition.